Isolation of Candida species in children and their biofilm-forming ability on nano-composite surfaces - Che Hussin, Harina Akila; Arshad, Nadiah; Nor Azemi, Siti Nor Humaira; Raja Sahrul Hishan, Raja Izzatun Nisa’; Wan Mohd Kamaluddin, Wan Nur Fatihah; Rismayuddin, Nurul Alia Risma; Muhamad Halil, Mohd Haikal; Ismail, Ahmad Faisal; Ali, Fatimah Maryam; Arzmi, Mohd Hafiz (Kulliyyah of Dentistry, International Islamic University Malaysia, 2020)
Candida species including Candida albicans, Candida krusei and Candida glabrata are opportunistic microorganisms that inhabit oral cavity. The objective of this study is to determine the effect of dental caries on Candida spp. biofilm-forming ability on nano-composite with the hypothesis that dental caries enhances the colonization of Candida spp. To assess Candida spp. colonisation in the oral cavity of the paediatric patient, samples were obtained from 30 subjects aged five to six years old from Kuantan, Pahang, Malaysia. The samples were collected from buccal mucosa, palate and tooth surfaces using sterile swabs. 10 mL of patient’s saliva suspension was also collected. Following that, the samples were inoculated on CHROMagar and incubated for 24 h at 37 ºC. Candida biofilm of caries isolate C. albicans (HNFC2), and C. albicans ATCC 32354 were developed on three different types of nano-composites. The study showed that no C. albicans was isolated from the caries-free oral cavity while 76% of children with caries possessed Candida spp. 65% of the yeasts were isolated from the tooth surface. Only 35% of the total isolates were obtained from soft tissues, including palatal and buccal mucosa. C. albicans is the most isolated Candida spp. with 82% and 67% of the yeast were obtained from the tooth surface and buccal mucosa, respectively. Besides, HNFC2 significantly colonised the nano-composites more than the ATCC (P < 0.05). In the comparison of the three types of nano-composites, nano-hybrid-based containing pre-polymerised filler (cB) exhibited the least C. albicans HNFC2 cells colonisation with 7.7 x 10³ cells mL-1. In contrast, the nano-composite that contained bulk-filled nanohybrid (cC) was the most colonised with 14.3 x 10³ cells mL-1. In conclusion, dental caries enhances the colonization of Candida spp. in children's oral cavity, and that caries isolate form more biofilm on nano-composites compared to the lab strain C. albicans.